Fitness Promotion in a Jump Rope-Based Homework Intervention for Middle School Students: A Randomized Controlled Trial - Huang, Fang; Song, Ying; Zhao, Yingdong; Han, Yating; Fang, Qun (Frontiers in Psychology, 2022)
Physical activity (PA) homework offers a promising approach for students to be physically active after school. The current study aims to provide holistic insights into PA homework design and effects of implementation in practice. Ninety-three middle school students were randomly assigned to homework group (HG) or control group (CG). Participants in HG (n = 47) were requested to complete jump rope homework 3 times per week for 12 weeks, while their counterparts in CG attended one health education class every week. Homework sheet was used to provide instructions and record information for exercise behaviors during homework completion. Physical fitness tests were conducted to investigate effects of the jump rope homework on physical fitness of the middle school students. After the intervention, participants in HG reported moderate to vigorous PA during jump rope exercise. Average duration for each practice was approximate 48 minutes. The returned homework sheets accounted for 86.88% of all homework assignments, indicating a good completion rate. Compared with their counterparts in CG, participants performing jump rope exercise indicated greater improvement in speed, endurance, power, and core muscular endurance. Jump rope homework strengthened physical fitness for middle school students, which provided valuable addition to comprehensive school PA practice.